2020
DOI: 10.5603/pmpi.2020.0002
|View full text |Cite
|
Sign up to set email alerts
|

Depression and quality of life among cancer patients undergoing chemotherapy

Abstract: Background. Cancer is a leading cause of death globally and in Indonesia. Cancer itself and the treatment often cause physical and psychological changes that affect patients' quality of life (QoL). This study aimed to determine the level of depression and QoL in cancer patients. Material and methods. This cross-sectional study involved 94 respondents who had chemotherapy in a public hospital in Indonesia. The study was conducted from January to April 2018. The depression level was assessed using the Beck Depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Fear of susceptibility to infection, lockdown measures imposed, restricted social activities, mass media information overload, uncertainty about the pandemic situation, rumors about vaccination effects, and the fear of losing loved ones to COVID-19 are some of the fears expressed by the participants, all of which may act as contributory factors to their poor psychological state. Similarly, previous studies have indicated the significant negative influence that depression, anxiety, insomnia, and fatigue have on reducing QoL and causing sleep disturbances in cancer patients (Rochmawati et al, 2020 ; Strik et al, 2021 ; Yeo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 64%
“…Fear of susceptibility to infection, lockdown measures imposed, restricted social activities, mass media information overload, uncertainty about the pandemic situation, rumors about vaccination effects, and the fear of losing loved ones to COVID-19 are some of the fears expressed by the participants, all of which may act as contributory factors to their poor psychological state. Similarly, previous studies have indicated the significant negative influence that depression, anxiety, insomnia, and fatigue have on reducing QoL and causing sleep disturbances in cancer patients (Rochmawati et al, 2020 ; Strik et al, 2021 ; Yeo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 64%
“…Kemoterapi memberikan dampak berupa kelelahan dan gangguan psikososial (Oh & Cho, 2020). Sebagian besar pasien mangalami ganguan pada fisik, gangguan fisik (Rochmawati et al, 2020). Namun demikian kondisi tersebut tergantung dengan karakter setiap pasien.…”
Section: Pendahuluanunclassified
“…Patients with cancer can thus experience a high burden of both psychological and physical distress that adversely affects their perceived quality of life, a key indicator of perceived health [ 4 ]. Recent studies have shown that a majority of patients with cancer in Iran do not seek medical care until later stages of the disease [ 5 , 6 ]. Such delays in diagnosis and treatment not only increase mortality but also contribute to decrements in quality of life.…”
Section: Introductionmentioning
confidence: 99%